Back azimuth vehicle tracking using a new rotational sensor FG-500 - Yusheng Guo; Dongqing Li; Yalan Song; Dongming Zhang; Qingzhou Li (AIP Advances)
The fiber optic rotational seismometer based on the Sagnac effect is insensitive to translational motions. It can achieve miniaturization while maintaining low noise, broadband, and high sensitivity, which is conducive to the application and promotion of the measurement of rotational motions. Therefore, fiber optic rotational seismometers and traditional translational seismometers will complement each other, achieving the six component observation of ground motions. This will help us better extract seismic wavefield features, improving the accuracy of wavefield separation, back azimuth estimation, and source position inversion. In this paper, we first introduce the basic principle of fiber optic rotational measurement and the use of rotation components to obtain the back azimuth. Then, we analyze the related performance indicators of the newly developed rotational seismometer (FG-500). Finally, we use a practical case to introduce the application of rotational components in estimating the back azimuth.